Literature Review: Hubungan Pengaruh Kelelahan Kerja Terhadap Shift Kerja Pada Karyawan Pabrik Industri - Puan Arliza Azmy; Tiara Arianti; Suci Wulandari; Nurliyani Malau; Hilda Aprilia Azizi (Universitas Katolik Widya Karya Malang, 2023)
Every hospital, industry and other sector experiences shifts in activity on a regular basis, and if the pace of construction and progress of the plant continues, this is absolutely necessary for the foreseeable future. Each individual's experience of fatigue is unique and subjective. Various conditions can result in fatigue accompanied by a decrease in body capacity and endurance while on duty. This study aimed to investigate the relationship between work fatigue and shift work in industrial plant employees. The research method used was a survey using questionnaires distributed to employees of industrial factories working in a shift system. The results showed a significant relationship between work fatigue and shift work in employees of industrial plants. High job fatigue can have a negative impact on employees' physical and mental health, as well as increase the risk of workplace errors and accidents. These findings point to the importance of effective shift management in reducing burnout and improving employee well-being. This research contributes to the understanding of the relationship between work burnout and shift work in employees of industrial plants. The practical implication of this study is the importance of greater attention to shift management in order to maintain employee well-being and productivity..